Variabilidade espacial e diurna dos fluxos de CO2 em um estuário amazônico - BATISTA, Matheus Sacramento (2021)
Estuaries generally act as a source of CO2 to the atmosphere, due to the high charge of organic matter from the rivers. However, we understand very little about the dynamics of water-air CO2 flux (FCO2) in tropical regions, mainly in the Amazon region, where there are highly dynamic systems at various scales of time and space. Therefore, our main objective was determined the intensity of FCO2 in an Amazonic estuary dominated by macrotidal. We perform in situ measurements of the hydrological and biogeochemical parameters along a tidal cycle and were collected samples waters for the analysis of phosphate (PO4 3-) and silicate (Si), by spectrophotometric analysis in the visible range and determination of alkalinity in situ by the potentiometric method. Total alkalinity (AT), temperature, pH and salinity were used as input data to calculate the other parameters of the carbonate system using a software CO2sys. The carbonate system parameters and the FCO2 showed large diurnal and seasonal variability. The estuary acted as a net source of CO2 to the atmosphere with a lower release of CO2 in the dry period of 2019 with an average of 17.5 ± 28.2 mmol m-2 d-1 and a higher release of CO2 in the dry period of 2020, an average of 105.6 ± 66.1 mmol m-2 d-1. In addition, we observed that in high tides the estuary has a lower CO2 emission while in low tides the estuary has a higher CO2 emission. The main drivers of changes in the carbonate system in the estuary are processes of a smaller time scale such as a semidiurnal macrotidal cycle and physical and biogeochemical processes that occur within the estuary, other processes, such as biological activity, were not so expressive for the variability of the FCO2, in view of the discrete diurnal variation of PO4 3- and Si. These results show the importance of considering the short-term variability in FCO2 biogeochemical studies in estuaries, especially those dominated by macrotidal dynamic. Moreover, they also reinforce the importance of these environments as sources of CO2 into the atmosphere.